Solvable : a simple solution to complex problems - Chevallier, Arnaud, 1974-; Enders, Albrecht (Pearson, 2022)
Arnaud Chevallier is Professor of Strategy at IMD. He prepares executives for the strategic challenges that corporations face in today’s dynamic global marketplace by helping them make better decisions in volatile and uncertain conditions. At IMD, he directs the Global Management Foundations and the Foundation Stage Singapore programs that are part of the EMBA curriculum. He has consulted with multiple organizations across industries, including Facebook, SAP, STADA, and Shell. Prior to his work at IMD, he served in various academic leadership positions at Rice University and the University of Monterrey. Before joining academia, Arnaud worked in Accenture’s Strategy and Business Architecture division, out of Houston and London. Albrecht Enders is Professor of Strategy and Innovation and Dean of Programs and Innovation at IMD. His major research, teaching and consulting interests are in the areas of managing discontinuous change and top team strategy development processes. Albrecht has worked for clients from different industries, including ABB, Agathon, Deloitte, Deutsche Bank, Siemens, Douglas Holding, Honda, ICBC, Novartis, MTR HongKong, Roland Berger, Safran, Skanska, Stora Enso, Telenor, Thyssen Krupp, TUI, Vodafone and VTT. In addition to running highly customized company-specific programs that focus on corporate transformation, he also directed the Advanced Strategic Management Program, one of IMD's core general management programs. Before coming to IMD, he spent three years as a consultant with The Boston Consulting Group in the company's Cologne office where he worked on projects in financial services, energy and industrial goods. These projects focused on strategy development, reorganization and efficiency improvement.